Effects of monovalent cations on folding kinetics of G-quadruplexes. Issue 4 (12th July 2017) - You, Jing; Li, Hui; Lu, Xi-Ming; Li, Wei; Wang, Peng-Ye; Dou, Shuo-Xing; Xi, Xu-Guang
Abstract : G-quadruplexes are special structures existing at the ends of human telomeres, the folding kinetics of which are essential for their functions, such as in the maintenance of genome stability and the protection of chromosome ends. In the present study, we investigated the folding kinetics of G-quadruplex in different monovalent cation environments and determined the detailed kinetic parameters for Na + - and K + -induced G-quadruplex folding, and for its structural transition from the basket-type Na + form to the hybrid-type K + form. More interestingly, although Li + was often used in previous studies of G-quadruplex folding as a control ion supposed to have no effect, we have found that Li + can actually influence the folding kinetics of both Na + - and K + -induced G-quadruplexes significantly and in different ways, by changing the folding fraction of Na + -induced G-quadruplexes and greatly increasing the folding rates of K + -induced G-quadruplexes. The present study may shed new light on the roles of monovalent cations in G-quadruplex folding and should be useful for further studies of the underlying folding mechanism.